2020
DOI: 10.1186/s43088-019-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary health indices and diabetes risk scores in undergraduate students of a private university in Nigeria

Abstract: Background: Cardiopulmonary health and its relationship with diabetes mellitus are very important but particularly underexplored in young undergraduate students of private Universities in Nigeria. This observational study investigated the effect of diabetic risk on cardiopulmonary health indices among healthy, consenting undergraduate students of a private university in Nigeria by a convenient sampling method. Cardiopulmonary health indices were assessed by anthropometry; cardiorespiratory fitness was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Diabetes mellitus (DM) is a metabolic and endocrine disease of chronic nature which arises from a lack of insulin secretion, action, or both. It is characterised majorly by chronic hyperglycaemia, disturbance in the intermediary metabolism of major macromolecules (carbohydrate, protein, and lipid), and vascular complications arising from organ/system dysfunction [ 1 , 2 ]. According to the International Diabetes Foundation (IDF), as of 2019, over 450 million adults were living with diabetes worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus (DM) is a metabolic and endocrine disease of chronic nature which arises from a lack of insulin secretion, action, or both. It is characterised majorly by chronic hyperglycaemia, disturbance in the intermediary metabolism of major macromolecules (carbohydrate, protein, and lipid), and vascular complications arising from organ/system dysfunction [ 1 , 2 ]. According to the International Diabetes Foundation (IDF), as of 2019, over 450 million adults were living with diabetes worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pieces of information show that hyperglycaemia-induced oxidative stress is a major player in the pathogenesis and progression of T2DM and its related complications; hence, tackling it cannot be overemphasised [11,17,[22][23][24][25]. With the increasing prevalence and incidence of T2DM in Nigeria and sub-Saharan Africa [2,26], oxidative stress has become a focal point of interest in diabetic research [11]. Despite the reported antioxidant activities of oral antioxidant agents such as vitamins, their usefulness in preventing diabetic complications is elusive as human studies have shown that they do not decrease oxidative stress [27][28][29].…”
Section: Introductionmentioning
confidence: 99%